Comprehensive school counseling programs : K-12 delivery systems in action - Dollarhide, Colette T. (Boston, Massachusetts : Pearson, 2012)
This book is designed to address changes in the professional environment since the publication of the first edition, and to address content improvements that have become obvious since the first edition.
Chapter1. The profession of school counseling -- Chapter2. Schools: social institution -- Chapter3. Moral, ethical and legal issues in school counseling -- Chapter4. Six qualities of comprehensive school counseling programs -- Chapter5. The ASCA national model -- Chapter6. Models of delivery system -- Chapter7. Accountability, action research and data driven outcomes -- Chapter8. Counseling -- Chapter9. Educating and curriculum delivery -- Chapter10. Collaboration and consultation -- Chapter11. Leadership, advocacy and coordination -- Chapter12. The delivery system in action -- Chapter13. Emerging issues for schools and students -- Chapter14. Personal and professional issues .
Includes bibliographical references and index.
Keywords: EDUCATIONAL COUNSELING